Bioaerosol exposure assessment in the workplace: the past, present and recent advances - Eduard, W.; Heederik, D.; Duchaine, C.; Green, B.J. (Royal Society of Chemistry, 2012)
Louis Pasteur described the first measurements of airborne microorganisms in 1861. A century later, the inhalation of spores from thermophilic microorganisms was shown to induce attacks of farmers' lung in patients with this disease, while endotoxins originating from Gram-negative bacteria were identified as causal agents for byssinosis in cotton workers. Further epidemiological and toxicological studies have demonstrated inflammatory, respiratory, and pathogenic effects following exposure to bioaerosols. Exposure assessment is often confounded by the diversity of bioaerosol agents in the environment. Microorganisms represent a highly diverse group that may vary in toxicity. Fungi and bacteria are mainly quantified as broad groups using a variety of viable and nonviable assessment methods. Endotoxins and β(1 → 3)-glucans are mainly measured by their activity in the Limulus amebocyte lysate assay, enzymes by immuno-chemical methods and mycotoxins by liquid chromatography-mass spectrometry. Few health-based occupational exposure limits (OELs) are available for risk assessment. For endotoxins, a health-based OEL of 90 endotoxin units m(-3) has been proposed in the Netherlands. A criteria document for fungal spores recently proposed a lowest observed effect level of 100,000 spores m(-3) for non-pathogenic and non-mycotoxin producing species based on inflammatory respiratory effects. Recent developments in bioaerosol assessment were presented at the Organic Dust Tromsø Symposium including molecular biological methods for infectious agents and organisms that are difficult to cultivate; studies of submicronic and hyphal fragments from fungi; the effect of biodiversity of microorganisms in asthma studies; and new/improved measurement methods for fungal antigens, enzymes and allergens. Although exposure assessment of bioaerosol agents is complex and limited by the availability of methods and criteria, the field is rapidly evolving.